Palmitic acid induces neurotoxicity and gliatoxicity in SH-SY5Y human neuroblastoma and T98G human glioblastoma cells - Ng, Yee-Wen; Say, Yee-How (PeerJ, 2018)
Background Obesity-related central nervous system (CNS) pathologies like neuroinflammation and reactive gliosis are associated with high-fat diet (HFD) related elevation of saturated fatty acids like palmitic acid (PA) in neurons and astrocytes of the brain. Methods Human neuroblastoma cells SH-SY5Y (as a neuronal model) and human glioblastoma cells T98G (as an astrocytic model), were treated with 100–500 µM PA, oleic acid (OA) or lauric acid (LA) for 24 h or 48 h, and their cell viability was assessed by 3-(4,5-dimetylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The effects of stable overexpression of γ-synuclein (γ-syn), a neuronal protein recently recognized as a novel regulator of lipid handling in adipocytes, and transient overexpression of Parkinson’s disease (PD) α-synuclein [α-syn; wild-type (wt) and its pathogenic mutants A53T, A30P and E46K] in SH-SY5Y and T98G cells, were also evaluated. The effects of co-treatment of PA with paraquat (PQ), a Parkinsonian pesticide, and leptin, a hormone involved in the brain-adipose axis, were also assessed. Cell death mode and cell cycle were analyzed by Annexin V/PI flow cytometry. Reactive oxygen species (ROS) level was determined using 2′,7′-dichlorofluorescien diacetate (DCFH-DA) assay and lipid peroxidation level was determined using thiobarbituric acid reactive substances (TBARS) assay. Results MTT assay revealed dose- and time-dependent PA cytotoxicity on SH-SY5Y and T98G cells, but not OA and LA. The cytotoxicity was significantly lower in SH-SY5Y-γ-syn cells, while transient overexpression of wt α-syn or its PD mutants (A30P and E46K, but not A53T) modestly (but still significantly) rescued the cytotoxicity of PA in SH-SY5Y and T98G cells. Co-treatment of increasing concentrations of PQ exacerbated PA’s neurotoxicity. Pre-treatment of leptin, an anti-apoptotic adipokine, did not successfully rescue SH-SY5Y cells from PA-induced cytotoxicity—suggesting a mechanism of PA-induced leptin resistance. Annexin V/PI flow cytometry analysis revealed PA-induced increase in percentages of cells in annexin V-positive/PI-negative quadrant (early apoptosis) and subG0-G1 fraction, accompanied by a decrease in G2-M phase cells. The PA-induced ROS production and lipid peroxidation was at greater extent in T98G as compared to that in SH-SY5Y. Discussion In conclusion, PA induces apoptosis by increasing oxidative stress in neurons and astrocytes. Taken together, the results suggest that HFD may cause neuronal and astrocytic damage, which indirectly proposes that CNS pathologies involving neuroinflammation and reactive gliosis could be prevented via the diet regimen.
Keywords: High-fat diet; Palmitic acid; Neuron; Astrocyte; Apoptosis; Oxidative stress